2021
DOI: 10.1124/jpet.121.000535
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Receptor Activation Rescues Opioid-Induced Respiratory Depression by Systemic Fentanyl in the Rat

Abstract: Introduction (426) Discussion (2062) d) Nonstandard abbreviations: dimethyl sulfoxide (DMSO), mean arterial pressure (MAP), opioid-induced respiratory depression (OIRD), phrenic nerve activity (PNA), vasopressin type 1a receptor (V1aR), vasopressin type 1a receptor antagonist (Phenylac 1 , D-Tyr(Et) 2 , Lys 6 , Arg 8 , des-Gly 9 )-Vasopressin trifluoroacetate (V1aRX) e) Recommended Section Assignment: Drug Discovery and Translational Medicine This article has not been copyedited and formatted. The final versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Interestingly, while the efficacy of the highest OT dose (32 ug) demonstrated a decrease in efficacy when compared to lower doses, this inversion was prevented by the addition of Mg 2+ . Inverted U dose responses have been widely reported for various systems, including social recognition (Benelli et al, 1995), opioidinduced respiratory depression (Brackley & Toney, 2021), and, very recently, in an autism spectrum clinical trial (Yamasue et al, 2022). This decrease in efficacy at higher doses of OT may be instrumental in the difficulty in demonstrating clear efficacy of intranasal OT in many clinical studies, where a moderate effect is seen with low doses, but higher doses do not show an improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while the efficacy of the highest OT dose (32 ug) demonstrated a decrease in efficacy when compared to lower doses, this inversion was prevented by the addition of Mg 2+ . Inverted U dose responses have been widely reported for various systems, including social recognition (Benelli et al, 1995), opioidinduced respiratory depression (Brackley & Toney, 2021), and, very recently, in an autism spectrum clinical trial (Yamasue et al, 2022). This decrease in efficacy at higher doses of OT may be instrumental in the difficulty in demonstrating clear efficacy of intranasal OT in many clinical studies, where a moderate effect is seen with low doses, but higher doses do not show an improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothalamic hormone, which has been studied for its ability to reverse opioid-induced respiratory depression, is the neuropeptide oxytocin. 29 In chloralose/urethane anesthetized, paralyzed, vagotomized, 100% oxygenventilated rats, the effect of intravenous oxytocin and the nonpeptide oxytocin receptor agonist and weak vasopressin receptor antagonist WAY-267464 were assessed on phrenic REVIEW ARTICLE nerve activity after a fentanyl dose sufficient to silence phrenic nerve activity. Oxytocin displayed a bell-shaped response curve in its ability to reverse phrenic nerve activity with maximal reversal at low dose but absence of reversal at high dose.…”
Section: Oxytocin Receptor Agonistsmentioning
confidence: 99%
“…Intravenous infusions of AVP transiently decrease pulmonary ventilation and phrenic nerve activity in conscious dogs ( Ohtake and Jennings, 1993 ), anesthetized and awake rats ( Louwerse and Marshall, 1993 ; Walker and Jennings, 1998 ; Żera et al, 2018 ; Brackley and Toney, 2021 ) and fetal lambs ( Bessho et al, 1997 ). Recently published pilot study in patients with autosomal dominant polycystic kidney disease showed that upon initiation of treatment with tolvaptan, a selective V2R antagonist, plasma copeptin level increased 6-fold and this was associated with a modest but significant increase in arterial carbon-dioxide and plasma acidity ( Heida et al, 2021 ), suggestive of ventilatory inhibition by increased AVP levels in the bloodstream and enhanced stimulation of V1 receptors, which were not blocked by tolvaptan.…”
Section: The Respiratory Effects Of Vasopressinmentioning
confidence: 99%
“…The inhibitory effects of AVP on the respiratory activity depend on V1aRs, as blockade of these receptors with selective antagonists completely prevents changes in pulmonary ventilation induced by systemic administration of AVP in anesthetized rats ( Louwerse and Marshall, 1993 ; Żera et al, 2018 ; Brackley and Toney, 2021 ). Furthermore, administration of V1aR antagonists may result in the increase in pulmonary ventilation in awake dogs ( Walker and Jennings, 1994 ).…”
Section: The Respiratory Effects Of Vasopressinmentioning
confidence: 99%
See 1 more Smart Citation